THE ROLE OF OUTSTANDING CULTURAL AND EDUCATIONAL ACTIVITIES OF THE END XIX- EARLY XX CENTURY IN THE STRUGGLE FOR UKRAINIAN SCHOOL AND NATIONAL EDUCATION - N.P. Meshcheryakova (Academy of Cognitive and Natural Sciences, 2004)
Generalized description of cultural and educational and pedagogical activities of the prominent Ukrainian representatives of the culture and enlightenment at the close of the XlXth and at the beginning of the XXth century is in this article. Their role in the struggle for Ukrainian schools and national education is defined in the present article.